2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions of Stroke Patients with Percutaneous Endoscopic Gastrostomy Feeding Tubes

Abstract: Objectives A critical mission of acute care hospitals is to reduce hospital readmissions to improve patient care and avoid monetary penalties. We speculated that stroke patients with enteral tube feeding are high-risk patients and sought to evaluate their hospital readmissions. Methods We analyzed archival hospital billing data from stroke patients discharged from acute care hospitals in Florida in 2012 for 30- and 60-day readmission rates, 30-day readmission rates by discharge destination, most frequent pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
2
19
1
Order By: Relevance
“…Prior studies have found a greater likelihood of PEG tube complications and hospital readmissions with advanced age. 8 Also, from the FOOD trials (Feed or Ordinary Diet), a comparison of early feeding via PEG versus nasogastric tube and delayed PEG, if needed, demonstrated that early PEG feeding was associated with a borderline increased risk of death or poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found a greater likelihood of PEG tube complications and hospital readmissions with advanced age. 8 Also, from the FOOD trials (Feed or Ordinary Diet), a comparison of early feeding via PEG versus nasogastric tube and delayed PEG, if needed, demonstrated that early PEG feeding was associated with a borderline increased risk of death or poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing hospital readmissions is not only a main incentive of acute care hospitals who are penalized for 30‐day readmissions through the Medicare Hospital Readmission Reduction Program but also in the interest of patients because readmissions are a surrogate for quality of care. Although several factors other than PEG tube placement may contribute to hospital readmissions in stroke patients, we found in a previous study that PEG tube placement was an independent risk factor for hospital readmissions in stroke patients …”
Section: Introductionmentioning
confidence: 59%
“…Besides discharge location, number of comorbidities, hospital length of stay (LOS), and stroke type were predictive for 30‐day readmissions. To the best of our knowledge, this is the only study that assessed hospital readmissions of stroke patients with PEG tube placement and that identified opportunities to prevent future readmissions . Our findings emphasize that stroke patients with a PEG tube are at risk for hospital readmissions because of clinically significant postacute care complications.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Major life-threatening complications occur in up to 3%[5,6]. In addition, PEG placement after stroke may be associated with increased early readmission rates, poor long-term outcomes, and mortality[7–10]. …”
Section: Introductionmentioning
confidence: 99%